PENGARUH E-MARKETING, KEPERCAYAAN KONSUMEN DAN EWOM TERHADAP KEPUTUSAN PEMBELIAN ONLINE PRODUK FASHION DI MARKETPLACE SHOPEE DI YOGYAKARTA - Tiara; Audita Nuvriasari (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to analyze influence of e-marketing, consumer trust, and e-WOM on online purchasing decisions fashion products in the Shopee marketplace. This research was conducted with a quantitative approach. Primary data collection was carried out by distributing questionnaires to a sample 100 respondents at least 17 years old and purchasing fashion products online in the Shopee marketplace for the past 1 year during which this research was conducted. The results of the Instrument Test stated that the data in this study were valid and reliable on The results of the Classical Assumption Test stated that the data in this study were normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study indicate that e-marketing has a positive and significant effect on online purchasing decisions fashion products in the Shopee marketplace with a significance level of 0.000 < 0.05. Consumer trust has no positive or significant effect on online purchasing decisions fashion products in the Shopee marketplace with a greater significance level of 0.997 > 0.05. Then e-WOM has a positive and significant effect on online purchasing decisions fashion products in the Shopee marketplace with a significance level of 0.009 <0.05.